Development of Integrated Farming Businesses Based on Zero Waste Agriculture in Parigi Moutong Regency - Burhanuddin Nasir; Irwan Lakani; Najamudin Najamudin; Sitti Sabariyah; Sri Anjar Lasmini; Moh. Syahrul Asdar; I Putu Suci Astawa; Ilham Akbar; I Kadek Duis Tiana (LPPM Universitas Ma Chung, 2021)
Zero waste agriculture is an agricultural concept oriented around the decomposition cycle of organic materials which integrates agricultural and livestock systems to reprocess waste material. Agricultural waste is used as animal feed while livestock waste/excrement is reprocessed into organic fertilizers. The Regional Partnership Service Program (PKW) aims to assist farmers in developing integrated farming businesses based around zero waste agriculture. PKW was held between May and July 2021 in Tindaki Village, South Parigi District, Parigi Moutong Regency. The implementation of this regional partnership program was carried out through a Participatory Action Programs approach, where partners are directly involved in the adoption and application of the various skills that had been developed. The procedure for activity implementation was carried out through several stages, namely: (a) counseling on zero waste agriculture, (b) training in and application of zero waste agriculture technology in the form of demonstration plots for the application of technological products, (c) coaching and mentoring, and (d) the utilization stage of technology product. The findings from the implementation concluded that the agricultural development training based on zero waste agriculture was a success, and the technology had been adopted by the community, marked by the ability to make and develop compost and liquid organic bio-urine fertilizers. Both types of organic fertilizers had been applied in the demonstration plots to assess their effectiveness in reducing the use of inorganic fertilizers. Rice production is equivalent to 5.6 tons/ha and 6 tons/ha in conventional land. These results show potential benefits for farmers, particularly regarding lower production costs compared to the usage of conventional land. Zero waste agriculture is a method of farming and livestock raising that utilizes their waste products for energy production.